Uruguay's investment law: fiscal policy showing performance of interest for study in Costa Rica (National Administration Journal, 2022)
The Investment Law of Uruguay is analyzed and recognized studies are presented that account for the social and productive performance of its fiscal incentives. It is studied how its benefits compensate its fiscal sacrifices, strengthen the productive environment and promote exports. Costa Rica also has tax incentives for foreign investment with its free trade zone system and promotes exports with excellent results, but does not establish performance parameters. The relevance of the study of Uruguay’s experience is established because its analysis and discussion could serve to enrich the fiscal incentives system in Costa Rica.
Keywords: Tax incentives; import substitution; performance indicators; development model; neoliberal policies